Built environmental correlates of cycling for transport across Europe. (March 2017) - Mertens, Lieze; Compernolle, Sofie; Deforche, Benedicte; Mackenbach, Joreintje D.; Lakerveld, Jeroen; Brug, Johannes; Roda, Célina; Feuillet, Thierry; Oppert, Jean-Michel; Glonti, Ketevan; Rutter, Harry; Bardos, Helga; et al.
Abstract: This cross-sectional study aimed to determine which objective built environmental factors, identified using a virtual neighbourhood audit, were associated with cycling for transport in adults living in five urban regions across Europe. The moderating role of age, gender, socio-economic status and country on these associations was also investigated. Overall, results showed that people living in neighbourhoods with a preponderance of speed limits below 30 km/h, many bicycle lanes, with less traffic calming devices, more trees, more litter and many parked cars forming an obstacle on the road were more likely to cycle for transport than people living in areas with lower prevalence of these factors. Evidence was only found for seven out of 56 possible moderators of these associations. These results suggest that reducing speed limits for motorized vehicles and the provision of more bicycle lanes may be effective interventions to promote cycling in Europe. Highlights: Speed limits below 30 km/h were associated with more cycling for transport. The presence of bicycle lanes was associated with more cycling for transport. These associations were similar across different subgroups.